The Interaction between Design Features and Learners’ Goals: A Case Study of a Science Museum Game - Cathy Tran; Ole Smørdal; AnneMarie Conley (Interaction Design and Architecture(s), 2016)
The design features of an educational game interact with students’ goals to influence their behaviors, and reciprocally, the outcomes of those behaviors dynamically shape their goals. Our study assessed the process of goal pursuit through a fine-grained analysis of motivation using self reports, interviews, and videos. Findings revealed patterns of engagement and disengagement that reflected students’ self-reported achievement goals of mastering the content knowledge, avoiding looking incompetent, and/or outperforming others. Those goals behaviorally manifested in the choices that students made about which information to focus on and the types of information to seek while playing a game. To inform future development of educational games, we present a typology of information-seeking behaviors and highlight key design features that support and hinder the pursuit of different goals. These insights expand our understanding of the underlying mechanisms that make balancing learner and player experiences challenging and provides guidance for that integration.